APPLICATION OF THE CRT (CULTURALLY RESPONSIVE TEACHING APPROACH IN IMPROVING THE PERSONAL LETTER WRITING SKILLS OF STUDENTS OF STATE SENIOR HIGH SCHOOL 2 LHOKSEUMAWE, ACEH - T. Muntazar; Meri Hari Yanni; Mawardi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aimed to investigate the effectiveness of the Culturally Responsive Teaching (CRT) approach in enhancing the personal letter-writing skills of high school students. A classroom action research design was employed with a sample of Class X students at SMA Negeri 2 Lhokseumawe. Data were collected through observations, assessments of personal letter-writing skills, and photo and video documentation. Both qualitative and quantitative descriptive analyses were conducted. The findings revealed a significant improvement in students' personal letter-writing skills across all assessed aspects following the implementation of the CRT approach. Specifically, in Cycle 1, 64.51% of students demonstrated incomplete letter-writing skills. However, in Cycle 2, this percentage decreased to 19%, with 81% of students achieving complete letter-writing skills. These results demonstrate the efficacy of the CRT approach in improving the personal letter-writing abilities of Class X students at SMA Negeri 2 Lhokseumawe